Review: Private food assistance in high income countries: A guide for practitioners, policymakers, and researchers. (August 2022) - Byrne, Anne T.; Just, David R.
Highlights: In an introduction to a special issue on private food assistance in high income countries, the authors detail the scope, nature, and impacts of these programs with a primary focus on food banks and pantries. The US appears to have the most far-reaching private food assistance network among the countries studied, but other high income countries have significant programs. Research on private food assistance has been varied and often limited by data that is localized or sparse. Research on private food assistance clients emphasizes characteristics like food security, poverty, and health. Research on private food assistance providers emphasizes offerings, client accessibility, supply chains, and food waste. Abstract: While private food assistance has long been a key component of the social safety net in many parts of the world, the literature examining the organization and effectiveness of private food assistance is relatively small with some substantial contributions coming only recently. In this article we describe the literature on private food assistance in high income countries, largely focusing on food banks and pantries. We offer an overview of the scope and nature of these services, their management and clientele. We also describe trends, opportunities, and limitations in research on private food assistance.